Japan (London : Dorling Kindersley Limited, 2019)
Discover Japan with this essential travel guide, designed to help you create your own unique trip and to transport you to this fascinating country before you've even packed your case - catch the buzz of futuristic Tokyo, step back in time in Kyoto, hike in mountainous Hokkaido or snorkel in Okinawa's clear waters. The DK Eyewitness Guide to Japan covers the must-see sights and the hidden backstreets, so you won't miss a thing.
Includes index
Primary
Keywords: Japan; Japan -- Guidebooks